Development of BET inhibitors as potential treatments for cancer: A search for structural diversity. (15th July 2021) - Hill, Matthew D.; Fang, Haiquan; Tokarski, John; Fanslau, Carolynn; Haarhoff, Zuzana; Huang, Christine; Kramer, Melissa; Menard, Krista; Monereau, Laura; Morrison, John; Ranasinghe, Asoka; Shields, Eric E.; et al.
Graphical abstract: Abstract: We describe our efforts to identify structurally diverse leads in the triazole-containing N1-carboline series of bromodomain and extra-terminal inhibitors. Replacement of the N5 "cap" phenyl moiety with various heteroaryls, coupled with additional modifications to the carboline core, provided analogs with similar potency, improved pharmacokinetic properties, and increased solubility compared to our backup lead, BMS-986225 (2 ). Rapid SAR exploration was enabled by a convergent, synthetic route. These efforts provided a potent BET inhibitor, 3-fluoropyridyl 12, that demonstrated robust efficacy in a multiple myeloma mouse tumor model at 1 mg/kg.